WaterCopilot: a water management AI virtual assistant for the Limpopo River Basin Digital Twin - technical guide - Vickneswaran, Keerththanan; Retief, H.; Padilha, R.; Dickens, Chris; Silva, Paulo; Garcia Andarcia, Mariangel (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2024)
The present document provides a comprehensive overview of the development, architecture, and capabilities of the Limpopo Digital Twin Chatbot or Copilot (WaterCopilot). WaterCopilot is an AI-driven virtual assistant designed to enhance data accessibility and support decision-making for water management in the Limpopo River Basin (LRB). It has been developed through collaboration between the International Water Management Institute (IWMI) and Microsoft Research. WaterCopilot integrates advanced natural language processing with real-time data retrieval to address key challenges in water resource management, including fragmented information sources, manual data processing, and delays in response.